Anti-inflammatory effects of shikonin in human periodontal ligament cells. (1st January 2018) - Fan, Chen; Zhang, Xufang; Upton, Zee
Abstract: Context: Shikonin (SHI), an active component extracted from Radix Arnebiae, has been reported to possess anti-inflammatory properties in various cells. However, its effect on lipopolysaccharide (LPS)-stimulated human periodontal ligament cells (hPDLCs) is unknown. Objective : To investigate the effects of SHI on the expression of inflammatory related cytokines in LPS-stimulated hPDLCs. Materials and methods: The effects of SHI (0.125, 0.25, 0.5, 1, and 2 μg/mL) on hPDLCs proliferation for 1, 3 and 7 days were measured using 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. The expression of interleukin-1 (IL-1), IL-6, tumor necrosis factor-α (TNF-α), matrix metalloproteinase-2 (MMP-2), MMP-9 and cyclooxygenase-2 (COX-2) were detected in hPDLCs following SHI treatment (0.25 and 0.5 μg/mL) using Quantitative Reverse Transcriptase Polymerase Chain Reaction (qRT-PCR). The signaling pathways triggered by SHI in hPDLC were evaluated using western blotting. Results: LD50 of SHI is 1.7 μg/mL (day 1) and 1.1 μg/mL (day 3 and 7) in hPDLCs. No morphological changes were observed when hPDLCs were treated with LPS only (1 μg/mL) or LPS with SHI (0.25 and 0.5 μg/mL). Data from qRT-PCR suggests that SHI attenuates LPS-induced increases of IL-1, IL-6, TNF-α, MMP-2, MMP-9 and COX-2 in hPDLCs. Down-regulation of phosphorylated extracellular signal-regulated kinase (ERK) and nuclear factor-κB (NF-κB), and up-regulation of I-κB, were observed in LPS-stimulated hPDLCs after exposed to SHI at 0.25 or 0.5 μg/mL. Discussion and conclusions: SHI possesses anti-inflammatory effects in LPS-stimulated hPDLCs via phospho-ERK and NF-κB/I-κB signaling pathways; this suggests that SHI may hold potential as an anti-inflammatory agent against periodontitis.